Modulation of Serum Interleukin-18 Concentrations and Hepatitis B Virus DNA Levels During Interferon Therapy in Patients with Hepatitis B e-Antigen-Positive Chronic Hepatitis B - Sylvan, Staffan P.E.; Hellstrom, Ulla B. (Journal of interferon & cytokine research, 2010)
The aim of this study was (1) to determine plasma values of interleukin-18 (IL-18) in patients with different clinical manifestations of hepatitis B (HB) and (2) to analyze the correlation between presence of circulatory levels of IL-18 and levels of HB virus (HBV) DNA during interferon-alpha (IFN-α)-induced HBe seroconversion in patients with chronic HB (CHB). The IL-18 levels in serum did not significantly differ between healthy control subjects (99 ± 25 pg/mL), HB-immune patients (85 ± 33), and asymptomatic carriers of HB surface antigen (144 ± 44 pg/mL). In contrast, anti-HBe (HBV DNA <10⁴ copies/mL, 555 ± 248, P < 0.05), anti-HBe (HBV DNA >10⁴ copies/mL, 280 ± 85, P < 0.05), and HBe-antigen-reactive (373 ± 108, P < 0.0001) patients with symptomatic CHB had significantly elevated levels in circulation compared with healthy control subjects (99 ± 25 pg/mL). An inverse correlation was found between serum HBV DNA copies and IL-18 levels during therapy (r = -0.54, P < 0.001). We consistently observed an IFN-α-induced suppression of viral replication, which was followed by the alanine aminotransferase (ALT) flare. There was a significant increase in IL-18 production after the ALT flare, where the peak of IL-18 preceded or coincided with the time of HBe seroconversion in patients who cleared the virus. These results suggest that IL-18 is involved in the pathogenesis of CHB and that IFN-α therapy can augment the production of IL-18 in patients with CHB.